Searching for suitable catalysts for a passive direct methanol fuel cell cathode - Asteazaran, Mariano (2015)
Trimetallic PtMRu/C cathode catalysts with M ¼ Co or Fe obtained by an impregnation procedure using ethylene glycol and NaBH4 as reducing agent, with suitable activity for the oxygen reduction reaction (ORR) and improved tolerance to methanol, have been physically characterized by HRTEM, EDS and XPS. The examined nanoparticles have a small particle size and are well spread on the carbon support. Pt is mainly found as Pt(0) and Co, Fe and Ru are mostly oxidized. To study their durability and performance for ORR and methanol tolerance over time, the catalysts were subjected to an electrochemical accelerated stress test (AST), consisting in cycling the potential 2000 times. Polarization curves for ORR with and without methanol were recorded. After the AST the trimetallic PtMRu/C catalysts are able to keep their performance for ORR in the presence of methanol.